2020
DOI: 10.3991/ijet.v15i24.16667
|View full text |Cite
|
Sign up to set email alerts
|

Gamified Learning: Are Vietnamese EFL Learners Ready Yet?

Abstract: Given the strong empirical evidence in the field of education that confirms the relationship between the application of game elements and increased learning motivation, gamification has recently become a concept that starts drawing attention in the field of English language teaching (ELT). However, the topic of gamification is still under-presented in ELT research, especially in English as a foreign language (EFL) contexts. The current research ex-plores the extent to which Vietnamese EFL learners are familiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…It has been utilized in many empirical studies in more than ten non-Englishspeaking countries. Unlike some previous studies (Phuong, 2020;Govender and Arnedo-Moreno, 2021) which claimed that online gamification was mainly used to teach vocabulary, and very little used to teach content knowledge and English grammar, not to mention other aspects of English learning, the quantitative findings of this study were that gamification could be widely used in teaching vocabulary, grammar, listening, speaking, reading, writing, pronunciation, college English, and even English literature. This indicates the feasibility and practicality of using gamification in actual EFL/ESL classrooms.…”
Section: Discussioncontrasting
confidence: 85%
“…It has been utilized in many empirical studies in more than ten non-Englishspeaking countries. Unlike some previous studies (Phuong, 2020;Govender and Arnedo-Moreno, 2021) which claimed that online gamification was mainly used to teach vocabulary, and very little used to teach content knowledge and English grammar, not to mention other aspects of English learning, the quantitative findings of this study were that gamification could be widely used in teaching vocabulary, grammar, listening, speaking, reading, writing, pronunciation, college English, and even English literature. This indicates the feasibility and practicality of using gamification in actual EFL/ESL classrooms.…”
Section: Discussioncontrasting
confidence: 85%
“…Students, both boys and girls, are equally motivated to participate in digital games (Papastergiou, 2009). Studies in the world have confirmed many advantages when implementing digital game-based learning, but according to qualitative research in Cavus's Web of Science database, the application of games alone in developing strategy management skills, namely Business Strategy Games (BSG) and Learning Strategy Management still shows many limitations, so it is affirmed that there is a need to do more research on deploying business strategy game and learning strategy management [33].…”
Section: The Efficiency Criteria Of Digital Game-based Instructional Technologymentioning
confidence: 99%
“…The students from cohort 46 are freshmen who could be the least influenced by the social integration in the school time studying in the university. Reference [40] indicated that the most common thread for students' avoidance to study sophomore year is social integration. It can be inferred that students' motivation for continuous learning in the university, as well as their participation in the in-class activities, is affected by this thread.…”
Section: Discussionmentioning
confidence: 99%